What Is It Like to Be a Sequential Animal? Review of David Herman, ed. Animal Comics: Multispecies Storyworlds in Graphic Narratives - Doran, Thomas (Humanimalia, 2019)
David Herman, ed. Animal Comics: Multispecies Storyworlds in Graphic Narratives. London: Bloomsbury, 2018. 280 pp. $114 hc, $39.95 pbk.